Characterization And Modeling Of Pultruded Jute Fibre Reinforced Unsaturated Polyester Composite - Safiee, Sahnizam (2011)
Pultruded Jute Fibre Reinforced Unsaturated Polyester Composites (PJFRC) was prepared and examined stage by stage in this study. Three different fibre volume percent of PJFRC with 50, 60 and 70% were prepared using the pultrusion technique. The PJFRC with 70% of fibre volume percent was successfully produced and displayed a homogeneous fibre distribution before having a high attrition to the fibre surface if the fibre volume percent more than 70%. Analysis was done by means of mechanical analysis, dynamic mechanical analysis, thermal conductivity and thermal mechanical analysis.